Pengembangan Pendidikan Moderasi Beragama pada Usia Remaja - Haryanto, Rizki; Delon, Julian; Wahyudi, Wahyudi (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2023)
The aim of this study is to ascertain the progress of religious moderation education among adolescents and to identify any uncertainties they may have regarding religion and religious moderation. This study employs a literature review research methodology. The book